Development and assessment of an onsite large volume solid phase extraction (LV-SPE) device for the determination of pharmaceuticals and personal care products (PPCPs) in water - Xue Cheng; Ning Fang; Yuxi Ge; Wenchao Li; Yamei Hui; Zilong Tang; Yu Wan; Yuancheng Li (Emerging Contaminants, 2024)
It is essential to determine the occurrence of emerging organic contaminants (EOCs), such as pharmaceuticals and personal care products (PPCPs), in the ambient environment to address growing public concerns. However, such analysis is quite challenging due to the low trace level of such contaminants in water, which therefore requires several litres of water samples. In this study, a large volume solid phase extraction (LV-SPE) device was developed and evaluated for its performance in monitoring PPCPs as an example. Relatively good recoveries and reproducibility were obtained under specific operating conditions: a water sample volume of no more than 20 L, a flow rate not exceeding 120 mL/min, and a methanol elution volume of at least 30 mL. In addition, the results from the onsite enrichment approach using LV-SPE were compared with those from the conventional approach using a standard SPE device in the laboratory for real groundwater samples. Among the eight selected PPCPs (nalidixic acid, carbamazepine, bezafibrate, clofibric acid, sulfadiazine, sulfamethoxypyridazine, sulfamethazine and sulfamonomethoxine), LV-SPE approach detected more target compounds. While the detected concentrations were generally comparable, slightly higher concentrations were observed for carbamazepine, clofibric acid, sulfadiazine and sulfamethazine using the LV-SPE method. The developed LV-SPE device provides an alternative approach for trace analysis of PPCPs and may also be applicable for other emerging organic contaminants.